Re: Does Gadoterate Meglumine Cause Gadolinium Retention in the Brain of Children? A Case–Control Study. Issue 2 (10th January 2020) - Forget, Joachim; Pozeg, Polona; Meuli, Reto A.; Maeder, Philippe
Abstract : Level of Evidence: 5 Technical Efficacy: Stage 5 J. Magn. Reson. Imaging 2020;52:636–637.